VISUALISASI DAN PREDIKSI KEDATANGAN PENUMPANG NGURAH RAI MENGGUNAKAN METODE HOLT-WINTERS - Diaz Ridzky Anandianto; Wasino; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
I Gusti Ngurah Rai International Airport is one of the airports in Indonesia which is located in Bali which has a large number of passenger arrivals because Bali has many interesting tourist attractions to visit. I Gusti Ngurah Rai international airport data certainly has a large size so that Business Intelligence (BI) technology is needed, namely a dashboard to process this data and gain insight. Forecasting the number of passenger arrivals is also carried out in order to be able to analyze what the number of passenger arrivals would be like in the future. Therefore, in this case the dashboard was made using the prototyping method and data mining with forecasting or forecasting using the Holt-Winters triple exponential smoothing method. The smoothing parameters used are alpha = 0.3, beta = 0.01, and gamma = 0.01 with the MAPE result of 32.04%. With the visualization on the dashboard, it is hoped that it will make it easier for the company that manage the airport to monitor the number of passenger arrivals at I Gusti Ngurah Rai International Airport so that they are able to make decisions in managing the airport.